Donor-Derived CD4+ T Cells and Human Herpesvirus 6B Detection After Allogeneic Hematopoietic Cell Transplantation. (14th July 2020) - Hanson, Derek J; Xie, Hu; Zerr, Danielle M; Leisenring, Wendy M; Jerome, Keith R; Huang, Meei-Li; Stevens-Ayers, Terry; Boeckh, Michael; Koelle, David M; Hill, Joshua A
Abstract: We sought to determine whether donor-derived human herpesvirus (HHV) 6B–specific CD4 + T-cell abundance is correlated with HHV-6B detection after allogeneic hematopoietic cell transplantation. We identified 33 patients who received HLA-matched, non–T-cell–depleted, myeloablative allogeneic hematopoietic cell transplantation and underwent weekly plasma polymerase chain reaction testing for HHV-6B for 100 days thereafter. We tested donor peripheral blood mononuclear cells for HHV-6B–specific CD4 + T cells. Patients with HHV-6B detection above the median peak viral load (200 copies/mL) received approximately 10-fold fewer donor-derived total or HHV-6B–specific CD4 + T cells than those with peak HHV-6B detection at ≤200 copies/mL or with no HHV-6B detection. These data suggest the importance of donor-derived immunity for controlling HHV-6B reactivation. Abstract : We demonstrated that a higher number of donor-derived total and human herpesvirus (HHV) 6B–specific CD4 + T cells may reduce the risk for higher-level HHV-6B detection after allogeneic hematopoietic cell transplantation.